Complaint Handling Melalui Aplikasi Wargaku Di Kota Surabaya - Fatmawati, Febrina; Nafi’ah, Binti Azizatun (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Complaint handling is an important aspect that can improve the quality of work and service in an organization. In handling complaints there is also a process that is carried out systematically in order to produce and provide maximum results for the community. Therefore, the Surabaya City Government launched the Wargaku application (Wadah Aspirasi Rukun Tetangga Rukun Warga dan Kampung Unggul). The Wargaku application is an application that provides services to Surabaya City residents and as a communication medium between Surabaya City residents and the Surabaya City Government. However, in its use there are still obstacles and shortcomings after 3 (three) years of running, such as the settlement of complaints exceeding the SOP and inequality in terms of accessibility of using the application. This research aims to describe and analyze how complaint handling in managing complaints through the Wargaku application in Surabaya City. This research uses descriptive qualitative methods and for data collection techniques using observation, interviews and documentation. For data analysis is done through the stages of data collection, data reduction, data presentation and conclusion drawing. The results and conclusions of this study indicate that complaint handling in the management of complaints through the Wargaku application can be said to be quite effective and also in accordance with existing SOPs, but there are still several cases or obstacles felt by the complainant as a complaint.